On the Legitimacy of Single Women's Social Egg Freezing - Muling GUO; Gaohua CHEN (Yixue yu zhexue)
Although "The Egg Freezing Case" was settled in 2024, the issue of social egg freezing rights of single women that the case highlighted remains unresolved. This debate has given rise to two opposing views on whether the limitations on egg freezing could be relaxed. Analysis shows that reproductive rights are natural rights that should not be constrained by traditional norms. Regarding the "freedom debate", the one-dimensional understanding of reproductive freedom in the context of egg-freezing technology should be discarded, and its definition should be clarified based on the fundamental principles of bioethics. Outdated prohibitions are logically unclear in their wording, ambiguous in their nature, and ineffective as direct legal grounds. Only by clarifying the legitimacy of social egg freezing for single women from a multi-dimensional perspective, can society build consensus on diverse values, improve legislative protections, and safeguard the fundamental rights of single women.